Are Low Weight or Cardiopathy Contraindications for Thoracoscopic Repair of Esophageal Atresia with Tracheoesophageal Fistula? - Cadaval, Carlos; Molino, José Andrés; Guillén, Gabriela; López Fernández, Sergio; Hierro, Carmen López; Martos Rodríguez, Marta; Khan, Haider Ali; Vilardell, Elena; Andreu, Eva; Ruiz, César W.; López, Manuel (European Journal of Pediatric Surgery, 2023)
Background Thoracoscopic repair of esophageal atresia (EA) with tracheoesophageal fistula (TEF) is becoming an increasingly widespread technique; there is still controversy about its indication in certain patients. Our objective is to analyze if potential risk factors such as major congenital heart disease (CHD) or low birth weight (LBW) are a limitation to this approach.Methods Retrospective study (2017–2021) of patients with EA and distal TEF who underwent thoracoscopic repair were included. Patients with LBW less than 2,000 g or major CHD were compared with the rest.Results Twenty-five patients underwent thoracoscopic surgery. Nine patients (36%) had major CHD. Five of them (20%) were LBW less than 2,000 g, and only 8% (2/25) presented both risk factors. There were no differences in terms of operative time, conversion rate, tolerance evaluated with gasometric parameters (pO2, pCO2, pH) or complications (anastomotic leak and stricture, both early or during follow-up) in patients with major CHD and LBW (1,473 ± 319 vs. 2,664 ± 402 g). One conversion to thoracotomy was performed in a neonate weighing 1,050 g due to anesthetic intolerance. There was no recurrence of TEF. One patient died at the age of 9 months, due to major uncorrectable heart disease.Conclusion Thoracoscopic repair of EA/TEF is feasible technique in patients with CHD or LBW, with similar results to other patients. The complexity of this technique warrants individualizing the indication in each case.Level of Evidence IV.
Keywords: thoracoscopic; esophageal atresia; congenital heart disease; low birth weight; newborn